Development of Student Handbook on the Extraction of Secondary Metabolites Based on Premna serratifolia Research - Shella Auliany; Dini Hadiarti; Rizmahardian Ashari Kurniawan (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop a digital module on the extraction of secondary metabolites based on P. serratifolia research as a self-study resource for students. This study utilized the Thiagarajan 4D development model, which encompasses the stages of definition, design, and development without dissemination. Participants in the study comprised students from Universitas Muhammadiyah Pontianak, Akademi Farmasi Yarsi Pontianak, and Universitas Tanjungpura who had previously studied extraction materials. Subject matter, media, and language experts provided validity scores of 94.69%, 88%, and 84.37%, respectively, resulting in an average validity score of 89.02%, categorizing the student handbook as highly valid. Small and large group trials yielded practicality percentages of 93.81% and 93.69%, respectively, with an average score of 93.75%, indicating the student handbook high practicality. Consequently, the student handbook on secondary metabolite extraction based on P. serratifolia research is deemed highly valid and practical as a self-study resource on the topic.